Whose truffle is this? Distribution patterns of ectomycorrhizal fungal diversity in Tuber melanosporum brûlés developed in multi‐host Mediterranean plant communities. (14th February 2015) - Taschen, Elisa; Sauve, Mathieu; Taudiere, Adrien; Parlade, Javier; Selosse, Marc‐André; Richard, Franck
Summary: In the Mediterranean region, patches of vegetation recovering from disturbance and transiently dominated by shrubs produce one of the world's most prized fungi, the black truffle ( T uber melanosporum ). In these successional plant communities, we have fragmentary knowledge of the distribution of T . melanosporum in space among ectomycorrhizal (ECM) host species and in time. Molecular identification of hosts (Restriction Fragment Length Polymorphism) and fungi (Internal Transcribed Spacer sequencing) and quantification of T . melanosporum mycelium (quantitative Polymerase Chain Reaction) were employed to evaluate the presence of T . melanosporum on four dominant ECM host species ( Q uercus ilex, Q uercus    coccifera, A rbutus unedo, C istus albidus ) and the extent to which their respective ECM communities shared fungal diversity, over the course of development of truffle grounds, from recent unproductive brûlés to senescent ones where production has stopped. We found that truffle grounds host rich communities in which multi‐host fungal species dominate in frequency. When considering both ECM tips and soil mycelia, we documented a dynamic and spatially heterogeneous pattern of T . melanosporum distribution in soils and a presence of ECM tips restricted to Q . ilex roots. This study advances our knowledge of the ecology of T . melanosporum, and provides insight into the extent of ECM fungal sharing among plant species that dominate Mediterranean landscapes.